Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/kin.21353
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the nitric oxide oxidation between 288 and 323 K, under pressure, focus on the oxygen influence on the reaction rate constant

Abstract: The sequestration of carbon dioxide fumes from oxyfuel combustion is used to reduce significantly the carbon dioxide emissions from coal‐fired power plants. Impurities like nitric oxide, present in the fumes, can cause technical difficulties during the capture, the treatment, the transport, and the storage steps of the CO2 fumes. The purpose of this study is to better understand the oxidation of nitric oxide under pressure in the presence of carbon dioxide and in the experimental condition of flue gas treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…with k 0 = 1200 L 2 mol −2 s −1 and −E A /R = 530 ± 400 K. This reaction has been studied on the same equipment, in the same condition of pressure and temperature and without water in a previous paper. 16 The results obtained in this study are close to the values recommended by Atkinson.…”
Section: Methodssupporting
confidence: 89%
“…with k 0 = 1200 L 2 mol −2 s −1 and −E A /R = 530 ± 400 K. This reaction has been studied on the same equipment, in the same condition of pressure and temperature and without water in a previous paper. 16 The results obtained in this study are close to the values recommended by Atkinson.…”
Section: Methodssupporting
confidence: 89%
“…Their study reported that the selectivity of cis ‐pinane was more than 96.5%, and the catalyst can be reused eight times. Kinetic research is another effective way to improve the performance of the catalyst because it helps understand the progress of the reaction 12 and theoretically guides the optimization process 13 . Recently, microkinetics has become popular owing to their advantages in complex reaction networks 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic research is another effective way to improve the performance of the catalyst because it helps understand the progress of the reaction 12 and theoretically guides the optimization process. 13 Recently, microkinetics has become popular owing to their advantages in complex reaction networks. 14 Grilc and coworkers [15][16][17] used a microkinetic model to investigate the effects of supported catalysts on the hydrogenation and hydrodeoxygenation of the lignin-derived model compound eugenol.…”
Section: Introductionmentioning
confidence: 99%
“…which involves the formation of a dimer from two NO molecules. The dimer further reacts with O 2 to form two NO 2 molecules[117]. Although Mech 2 was included in the Konnov model and the CRECK model, some preliminary kinetic analyses (whose results will be included in a forthcoming publication from the authors' group) have indicated that the NO to NO 2 conversion around room temperature is still dominated by NO + NO + O 2 = NO 2 + NO 2 .…”
mentioning
confidence: 99%